Good clinical response to cemiplimab in a young patient with locally advanced cutaneous squamous cell carcinoma on preexisting recessive dystrophic epidermolysis bullosa - Ciurescu Daniel, Condruz Simina, Irimie Marius (Ljubljana : Slovene Welding Society, 2024)
Recessive dystrophic epidermolysis bullosa (RDEB) is a rare genetic skin disease caused by mutations in the type VII collagen gene (COL7A1; 3p21.31). Mutations in this gene lead to an alteration in function or reduced amounts of collagen VII. This alteration of collagen VII leads to skin fragility and lesions at minor injuries with difficult healing. Cutaneous squamous cell carcinoma (cSCC) is more frequent in patients with RDEB than in the general population because of chronic wound formation; it constitutes a major cause of morbidity and is often cited as a cause of death for these patients. There is little experience with the treatment of cSCC in patients with RDEB. We report the case of a 19-year-old female patient with RDBE and inoperable locally advanced cSCC of the left arm. Because of the lack of therapy options, therapy with cemiplimab was started at a dose of 350 mg administered intravenously every 3 weeks. A confirmed clinical response was observed after the second cycle of treatment with no toxicity. During follow-up, the patient had a notable clinical response with no auto-immune adverse reactions. This shows that cemiplimab has a good safety profile for cSCC in patients with RDEB and is a valuable therapy option.